PERSPEKTIF KELAS DALAM PERLAWANAN WARGA DESA WADAS TERHADAP RENCANA PEMBANGUNAN BENDUNGAN BENER - Ekayanta, Fredick Broven (Jurnal Ilmiah Widya Sosiopolitika; Vol 4 No 1 (2022): PERSPEKTIF KELAS DAN RADIKALISME, 2022)
Infrastructure development projects implemented by the government often have social impacts that are detrimental to community. This article analyzes how community reject the infrastructure development plan, by taking a case study of the Wadas residents' rejection of andesite mining and the Bener Dam. This article uses a class perspective in order to get comprehensive explanations from affected community. By using the theory of primitive accumulation, this article argues that rejection and resistance to infrastructure development plans is a response to the process of separation (removal from working conditions) in primitive accumulation that will occur. This article strengthens the theory of primitive accumulation which is characterized by the involvement of state power. From the Wadas case, the role of this power is to issue legal regulations, deploy officers, and act as implementers of the development project.